Risk assessment and control in engineered nanoparticles occupational exposure - Silva, Francisco (2013)
The huge research effort and common use of nanomaterials, being an opportunity for economic growth, pose health and safety problems. The research on the nanoparticles health effects performed during the last decade shows the possible harmfulness of several nanoparticles, including those already present in everyday use products. Although the increasing knowledge in the nanotoxicilogy field, and also the occupational hygiene responses in order to develop quantitative methods to evaluate nanoparticles exposure risk, there is a uncertainty climate. The use of qualitative risk assessment methods appears as a suitable way to deal with the uncertainties and to support decisions leading to the risk control. Among these methods, those based in control banding, such as the CB Nanotool and the Stoffenmanager Nano, seems to become applied more frequently. Furthermore, the design approach to safety can be a valuable way to establish the strategy to protect the workers’ health focusing in the production process in order to define the most effective measures to control the exposure risk.